2023
DOI: 10.1093/cid/ciad571
|View full text |Cite
|
Sign up to set email alerts
|

Are Contact Precautions “Essential” for the Prevention of Healthcare-associated Methicillin-Resistant Staphylococcus aureus?

Daniel J Diekema,
Priya Nori,
Michael P Stevens
et al.

Abstract: The recently updated SHEA/IDSA/APIC practice recommendations for MRSA prevention in acute care facilities list contact precautions (CP) for patients known to be infected or colonized with MRSA as an “essential practice”, meaning that it should be adopted in all acute care facilities. We argue that existing evidence on benefits and harms associated with CP do not justify this recommendation. There are no controlled trials that support broad use of CP for MRSA prevention. Data from hospitals that have discontinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…38 In particular, the environmental impact of the increased use of gowns and gloves, the effectiveness of which has yet to be demonstrated for MRSA. 14 According to the recommendations of the Society for Healthcare Epidemiology of America/Centers for Disease Control, active surveillance of MRSA on a hospital-wide scale can be used in conjunction with contact precautions to reduce the incidence of MRSA infection with moderate-quality evidence. 3 However, the reduction of MRSA transmission to other patients in the ward depends on a set of measures that must be taken into account to assess the benefits and drawbacks of a targeted screening protocol with a decreased loss of sensitivity and specificity.…”
Section: J O U R N a L P R E -P R O O F 11mentioning
confidence: 99%
See 1 more Smart Citation
“…38 In particular, the environmental impact of the increased use of gowns and gloves, the effectiveness of which has yet to be demonstrated for MRSA. 14 According to the recommendations of the Society for Healthcare Epidemiology of America/Centers for Disease Control, active surveillance of MRSA on a hospital-wide scale can be used in conjunction with contact precautions to reduce the incidence of MRSA infection with moderate-quality evidence. 3 However, the reduction of MRSA transmission to other patients in the ward depends on a set of measures that must be taken into account to assess the benefits and drawbacks of a targeted screening protocol with a decreased loss of sensitivity and specificity.…”
Section: J O U R N a L P R E -P R O O F 11mentioning
confidence: 99%
“…At this time, there is currently no international consensus on screening patients for MRSA upon admission. A recent study indicated that some acute care facilities have reported no negative consequences associated with discontinuing contact precautions for patients colonised with MRSA 14 . In addition, screening recommendations do not take into account the specificities of the geriatric population, despite the documented increased risk of infection and carriage in this type of patient.…”
Section: Introductionmentioning
confidence: 99%
“…12 It is worth mentioning that there remains active discussion about the necessity of universal CP for MRSA. 28,29 This controversy primarily arises from inadequate data as well as the difficulty in separating the effect of CP alone from other interventions often bundled with CP (eg, hand hygiene). 30 Due to the relatively rare detected transmission of MDRO organisms, large sample sizes are needed over long periods to optimally measure effectiveness, 31,32 and modeling is often used as an adjunct to study transmission.…”
Section: Isolation Measuresmentioning
confidence: 99%
“…Data continues to emerge about the psychological aspects of patient isolation, 36 though trial data suggests that CP has minimal impact on non-infectious adverse events. 37 Another non-infectious adverse event of increasing relevance is the environmental impact of contact precautions 29,38 this is an under-explored topic and research is needed to quantify the environmental impact of different CP scenarios (eg, universal vs targeted CP), and future modeling work should ideally incorporate environmental sustainability metrics (eg, carbon footprint, plastic waste burden) into cost-effectiveness models.…”
Section: Isolation Measuresmentioning
confidence: 99%
See 1 more Smart Citation